Does Job Stability Mediate the Relationship Between Intimate Partner Violence and Mental Health Among Low‐Income Women?. (28th October 2013) - Adams, Adrienne E.; Bybee, Deborah; Tolman, Richard M.; Sullivan, Cris M.; Kennedy, Angie C.
Abstract : Intimate partner violence (IPV) has detrimental consequences for women's mental health. To effectively intervene, it is essential to understand the process through which IPV influences women's mental health. The current study used data from 5 waves of the Women's Employment Study, a prospective study of single mothers receiving Temporary Assistance for Needy Families (TANF), to empirically investigate the extent to which job stability mediates the relationship between IPV and adverse mental health outcomes. The findings indicate that IPV significantly negatively affects women's job stability and mental health. Further, job stability is at least partly responsible for the damaging mental health consequences of abuse, and the effects can last up to 3 years after the IPV ends. This study demonstrates the need for interventions that effectively address barriers to employment as a means of enhancing the mental health of low‐income women with abusive partners.